Familial Hemophagocytic Lymphohistiocytosis in a Pediatric Patient Diagnosed by Brain Magnetic Resonance Imaging - van Egmond, M. E.; Vermeulen, R. J.; Peeters-Scholte, C.M.P.C. D.; Augoustides-Savvopoulou, P.; Abbink, F.; Boelens, J. J.; van der Knaap, M. S. (Neuropediatrics, 2011)
Familial hemophagocytic lymphohistiocytosis (fHLH) is an autosomal recessive disorder characterized by proliferation and infiltration of several organs by activated lymphocytes and macrophages. Without allogeneic stem cell transplantation, fHLH is fatal. We describe a previously healthy 11-month-old boy with a rapidly progressive encephalopathy. An older brother died at 8 months following a subacute encephalopathy diagnosed as meningoencephalitis. The family history led to the suspicion of a metabolic disease, but metabolic studies were unrevealing. MRI showed multiple inhomogeneous signal abnormalities in the cortex and white matter, most prominent in the cerebral hemispheres and around the dentate nucleus. Gadolinium-enhanced T1-weighted images showed a multitude of enhancing foci, suggestive of perivascular enhancement. Based on MRI pattern with multiple lesions, perivascular enhancement and family history, fHLH was suspected. DNA analysis showed that the patient was compound-heterozygous for the c.445 G>A (p.Gly149Ser) mutation in exon 1 and the c.757 G>A (p.Glu253Lys) mutation in exon 2 of the perforin 1 gene. The patient was treated according to the international HLH-2004 protocol (dexamethasone, etoposide, cyclosporine, intrathecal methotrexate and prednisolone) followed by allogeneic cord blood transplantation. He showed a significant neurological and radiological improvement. The reported case demonstrates that MRI pattern recognition can lead to early diagnosis of fHLH, with subsequent adequate treatment.
Keywords: familial hemophagocytic lymphohistiocytosis; magnetic resonance imaging; perivascular enhancement; allogeneic stem cell transplantation